2001
DOI: 10.2466/pms.2001.93.1.297
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Self-Esteem in Adolescent Ballet Dancers

Abstract: Body-image disturbances and low self-esteem have been implicated in the pathogenesis of eating disorders. This study investigated self-perception of body and personality among adolescent ballet dancers in a cross-sectional survey. Two questionnaires assessing "my body right now" and "my personality right now," using semantic differentials were completed by 90 ballet school students and 156 controls. Adolescent female dancers (ages 13 to 17 years) scored higher than age-matched controls and 11- to 12-yr. old pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 48 publications
2
26
0
3
Order By: Relevance
“…Self-esteem, which is considered a relevant protective factor in this model, was not a predictor of DE in elite athletes, in contrast to the other two groups. This was an unexpected result, especially due to the frequent association between DE and low self-esteem in athletes of aesthetic sports (e.g., [14,15]). Furthermore, social pressure (which is related to peer pressure, as mentioned) is the strongest predictor of self-esteem in the three groups.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Self-esteem, which is considered a relevant protective factor in this model, was not a predictor of DE in elite athletes, in contrast to the other two groups. This was an unexpected result, especially due to the frequent association between DE and low self-esteem in athletes of aesthetic sports (e.g., [14,15]). Furthermore, social pressure (which is related to peer pressure, as mentioned) is the strongest predictor of self-esteem in the three groups.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study of female collegiate athletes showed that low levels of selfesteem, but not high levels of perfectionism, were associated with higher levels of disordered eating [13]. Some studies show a clear correlation between low body image satisfaction and ED symptoms among athletes (e.g., [14,15]), even considering body image satisfaction a mediating variable for the social influence for thinness, anxiety about athletic performance, and negative appraisals of athletic achievement [16]. However, other studies report the absence of this correlation.…”
Section: Introductionmentioning
confidence: 99%
“…The higher dieting and body dissatisfaction may have been a result of their discipline. Female ballet students are less satisfied with their weight in comparison with their non-dancing peers 17 and often wish to decrease weight despite a low body mass index (BMI) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the other facilitating factors, athletic participation has often been linked to a higher prevalence of eating disorders, which are found to be particularly widespread among performers of certain types of sports or physical activities, such as ballet [11][12][13][14][15][16], gymnastics [17][18][19], running [20][21][22] and skating [23,24]. Several personality characteristics have been claimed to be associated both with eating disorders and sport participation: competitiveness, concern about performance, compulsive concern about body shape and perfectionism [25].…”
Section: Introductionmentioning
confidence: 99%